Highly effective Ru(II) and Os(II) half-sandwich complexes induce cytotoxicity in cancer cells through combined mitochondrial and endoplasmic reticulum stress - Hošek, Jan; Petrželová, Kamila; Héžová, Renata; Straková, Nicol; Kajabová, Simona; Nemec, Ivan; Šimečková, Pavlína; Pěnčíková, Kateřina; Mašek, Josef; Moncoľ, Ján; Štarha, Pavel (European journal of medicinal chemistry, 2025)
A series of ruthenium(II) and osmium(II) half-sandwich complexes was synthesized and characterized for its potential as a new class of anticancer agents. The complexes feature polycyclic aromatic hydrocarbon (PAH)-substituted Schiff bases and were rationally designed to combine the redox-modulating MoA of half-sandwich Ru, Rh, Os and Ir complexes, connected with their ability to induce the formation of various reactive oxygen species (ROS), with the ability of PAH-substituents to target and disrupt DNA. The complexes [Ru(η6-pcym)Cl(L)]PF6 (1-4) and [Os(η6-pcym)Cl(L)]PF6 (5-8) were stable in aqueous environments, in contrast to the rapid degradation observed for the co-studied rhodium(III) (9-12) and iridium(III) (13-16) [M(η5-Cp∗)Cl(L)]PF6 complexes; L = ethane-1,2-diamine-based Schiff bases (L1-L4) bearing two terminal PAH substituents 2-naphtyl (for L1), 9-anthracenyl (for L2), 9-phenanthrenyl (L3) or 1-pyrenyl (L4); pcym = 1-methyl-4-(propan-2-yl)benzene (p-cymene), Cp∗ = pentamethylcyclopentadienyl. Biological testing demonstrated that 1-8 possess significant antiproliferative activity against various lung cancer cell lines, including those resistant to cisplatin, with Os(II) complex 5 showing the highest cytotoxicity. Treatment with these complexes led to the activation of stress-related gene pathways, including unconventional endoplasmic reticulum stress, apoptotic signalling, and mitochondrial membrane depolarization. Activation of p21/GADD45A pathway indicates DNA-damage response, as well. Notably, these complexes did not induce significant inflammatory responses, a notable advantage over cisplatin. The results highlight the potential of Ru and Os half-sandwich complexes as alternative metallodrugs, capable of overcoming platinum resistance and minimizing inflammatory side effects. This study suggests that these compounds could serve as a promising class of anticancer agents for future clinical development.
Keywords: Ruthenium; Osmium; Endoplasmic reticulum; Mitochondria; protinádorové látky; Cell Line, Tumor; Cell Proliferation; reaktivní formy kyslíku; Structure-Activity Relationship; Drug Screening Assays, Antitumor; molekulární struktura; komplexní sloučeniny; Molecular Structure; vztah mezi dávkou a účinkem léčiva; Organometallic Compounds; vztahy mezi strukturou a aktivitou; ruthenium; stres endoplazmatického retikula; Reactive Oxygen Species; Coordination Complexes; lidé; Humans; Antiproliferative activity; osmium; proliferace buněk; screeningové testy protinádorových léčiv; Stress gene expression; Endoplasmic Reticulum Stress; nádorové buněčné linie; Dose-Response Relationship, Drug; mitochondrie; Antineoplastic Agents; organokovové sloučeniny